A biomimetic bilayer coating on laser-textured Ti6Al4V alloy with excellent surface wettability and biotribological properties for artificial joints. Issue 18 (15th September 2022) - Cui, Lingling; Li, Hang; Gong, Chenyang; Huang, Jiewen; Xiong, Dangsheng
Abstract: Titanium alloys with excellent mechanical properties and biocompatibility are widely used in surgical implants. However, due to its poor tribological properties, it is difficult to be used in joint bearing interfaces. Herein, mimicking the soft/hard hierarchical structure of articular cartilage/subchondral bone and the unique lubrication mechanisms of articular cartilage, a biomimetic bilayer coating consisting of a TiO2 layer and a hydrogel layer was fabricated on laser-textured Ti6Al4V alloy by laser surface texturing, thermal oxidation and ultraviolet radiation techniques. Meanwhile, a zwitterionic polymer (SBMA) was introduced into the hydrogel layer to provide hydration lubrication. The experimental results demonstrated that the introduction of SBMA greatly improved the hydrophilicity and compressive modulus of the hydrogel layer. Compared with Ti6Al4V, the Ti6Al4V-hydrogel bearing interface exhibited a lower friction coefficient (0.06) and better wear resistance when lubricated in deionized water. More importantly, this Ti6Al4V-hydrogel bearing interface could maintain stable and low friction coefficients when lubricated in different physiological solutions for a long-term friction (4 h), and the lowest friction coefficient (0.039) was measured in phosphate buffer (PBS) solution. The outstanding biotribological performance was mainly attributed to the biphasic and hydration lubrication mechanisms of the hydrogel layer. This study provides new insights into the development of Ti6Al4V bearing interfaces for artificial joints.